Graphite composite negative electrode material and preparation method and application thereof

The graphite composite anode material prepared through liquid phase coating and double helix electrospinning technology solves the problems of many hard carbon active points and defects, and achieves the improvement of high-temperature storage and rate performance, extends service life and improves safety performance.

CN119601613APending Publication Date: 2025-03-11JIANGSU JIYAO NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411529423.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the prior art, there are many active points and defects in hard carbon, which are not conducive to the problem of poor high-temperature storage and rate performance.

Method used

By liquid-phase coating graphite with coal asphalt in the presence of a molding agent, then mixing it with acidic functional additives and coupling agents, a composite fiber tow is formed by double helix electrospinning technology and pyrolytic treatment is performed to prepare graphite composite negative electrode material.

Benefits of technology

This method not only maintains the advantages of high energy density and low cost of graphite composite anode material, but also significantly improves its fast charging, cycling performance and high-temperature storage capabilities, extends service life, and improves safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601613A_ABST
    Figure CN119601613A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery material preparation, and discloses a graphite composite negative electrode material and a preparation method and application thereof. The method comprises the following steps: in the presence of a shaping agent, contacting graphite with coal pitch for liquid-phase coating to obtain a graphite-coated material; in the presence of an organic solvent I, contacting the graphite coating material with an acidic functional additive and a coupling agent for first mixing to obtain a solution A; in the presence of the organic solution I I, petroleum asphalt is in contact with an alkaline functional additive and ethidene diamine for secondary mixing, and a solution B is obtained; performing double-helix electrostatic spinning by taking the solution A and the solution B as an inner ring solution and an outer ring solution respectively to obtain a composite fiber tow; and performing pyrolysis treatment on the composite fiber tow to obtain the graphite composite negative electrode material. The graphite composite negative electrode material prepared by the method keeps the advantages of high energy density and low cost, takes into account the fast charge and cycle performance of the negative electrode material, and overcomes the defect of multiple active point defects of hard carbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery material preparation, and in particular to a graphite composite negative electrode material and a preparation method and application thereof. Background Art

[0002] With the rapid development of new energy electric vehicles and energy storage equipment, people are increasingly focusing on the research and development of high energy density batteries, and have higher requirements for the fast charging and high temperature storage performance of batteries. The negative electrode material has also become the core of battery research and development. The performance of current negative electrode materials in terms of fast charging and cycling cannot meet people's needs, which seriously restricts the promotion and use of lithium batteries. The smaller interlayer spacing of graphite materials makes Li + The rapid diffusion of graphite anode materials has been restricted, so the research and development of a graphite anode material that can meet the requirements of fast charging and high-temperature storage has become the focus and difficulty of current research.

[0003] In view of the research on hard carbon-coated graphite, hard carbon can improve the fast charging capability due to its large interlayer spacing. Therefore, the negative electrode material of hard carbon-coated graphite is an effective method to improve the performance of the negative electrode material. However, hard carbon has many active sites and defects, which is not conducive to high-temperature storage and circulation.

[0004] CN 117117126A discloses a method for preparing a soft carbon-coated hard carbon composite material, wherein any one of phenolic resin, furfural resin, epoxy resin, lignin and starch is used as the core component of the hard carbon-coated material, and any one of petroleum asphalt, coal asphalt and asphalt intermediate phase is used as the core component of the soft carbon raw material, and the usage ratio of the hard carbon raw material to the soft carbon raw material is 1: 1. This technical solution obtains a fibrous structural material of soft carbon-coated hard carbon by chemically connecting through acid-base reaction and coupling agent, thereby improving the electronic conductivity of the material, but it still has the disadvantages of relatively high cost, difficulty in large-scale use in actual enterprise application, and relatively poor cycle performance. Summary of the invention

[0005] The purpose of the present invention is to solve the problems in the prior art that hard carbon has many active sites and defects, is not conducive to high-temperature storage and has poor rate performance.

[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a graphite composite negative electrode material, the method comprising:

[0007] (1) contacting graphite with coal tar pitch in the presence of a plasticizer to perform liquid phase coating to obtain a graphite-coated material; and contacting the graphite-coated material with an acidic functional additive and a coupling agent in the presence of an organic solvent I to perform a first mixing to obtain a solution A;

[0008] and contacting petroleum asphalt with an alkaline functional additive and ethylenediamine in the presence of an organic solution ⅠⅠ to perform a second mixing to obtain a solution B;

[0009] (2) performing double helix electrospinning using the solution A and the solution B as the inner ring solution and the outer ring solution, respectively, to obtain a composite fiber bundle;

[0010] (3) The composite fiber bundle is subjected to pyrolysis treatment to obtain the graphite composite negative electrode material.

[0011] Wherein, in step (1), the liquid phase coating conditions include: temperature of 250-400°C, time of 2-6h, and rotation speed of 40-60rpm;

[0012] In step (2), the weight ratio of solution A to solution B is 1.5-2.5:1.

[0013] The second aspect of the present invention provides a graphite composite negative electrode material prepared by the method described in the first aspect.

[0014] The third aspect of the present invention provides the use of the graphite composite negative electrode material described in the second aspect in a soft-pack battery.

[0015] Through the above technical solution, the present invention has at least the following advantages:

[0016] The graphite composite negative electrode material prepared by the method for preparing a graphite composite negative electrode material provided by the present invention not only maintains its advantages of high energy density and low cost, but also takes into account the fast charging and cycle performance of the negative electrode material, and overcomes the disadvantages of many defects in hard carbon active sites.

[0017] In addition, this method not only produces fewer side reactions, ensuring the high-temperature storage and circulation of the graphite composite negative electrode material, further improving its electrochemical performance; but also the graphite composite negative electrode material has a large charge and discharge capacity, high efficiency, good rate performance, improved cycle performance, extended service life, and good safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The present invention provides a flow chart of the method for preparing the graphite composite negative electrode material. DETAILED DESCRIPTION

[0019] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0020] In the present invention, PVDF refers to “polyvinylidene fluoride” and NMP refers to “N-methylpyrrolidone”.

[0021] As mentioned above, the first aspect of the present invention provides a method for preparing a graphite composite negative electrode material, the method comprising:

[0022] (1) contacting graphite with coal tar pitch in the presence of a plasticizer to perform liquid phase coating to obtain a graphite-coated material; and contacting the graphite-coated material with an acidic functional additive and a coupling agent in the presence of an organic solvent I to perform a first mixing to obtain a solution A;

[0023] and contacting petroleum asphalt with an alkaline functional additive and ethylenediamine in the presence of an organic solution ⅠⅠ to perform a second mixing to obtain a solution B;

[0024] (2) performing double helix electrospinning using the solution A and the solution B as the inner ring solution and the outer ring solution, respectively, to obtain a composite fiber bundle;

[0025] (3) The composite fiber bundle is subjected to pyrolysis treatment to obtain the graphite composite negative electrode material.

[0026] Wherein, in step (1), the liquid phase coating conditions include: temperature of 250-400°C, time of 2-6h, and rotation speed of 40-60rpm;

[0027] In step (2), the weight ratio of solution A to solution B is 1.5-2.5:1.

[0028] The inventors of the present invention found during the research process that the graphite composite negative electrode material prepared by the method for preparing the graphite composite negative electrode material proposed in the present invention not only maintains its advantages of high energy density and low cost, but also takes into account the fast charging and cycle performance of the negative electrode material, and overcomes the shortcomings of hard carbon active sites and many defects; the reason may be that: the interlayer spacing between hard carbon and soft carbon is larger than that of graphite, which is more conducive to Li + The transmission of lithium ions improves the initial efficiency of the battery and thus improves the fast charging performance of the battery; the micropores of soft carbon can be used as active sites for lithium storage, which increases the diffusion coefficient of lithium ions in soft carbon, ensures the performance of cycling and fast charging, ensures the stability of graphite particles during charging and discharging, and solves the cycling problem; soft carbon has fewer defects and fewer side reactions, which ensures high-temperature storage and cycling, and further improves its electrochemical performance; soft carbon has a low and stable charging and discharging platform, large charging and discharging capacity, high efficiency, and good cyclability, which can extend the life; the carbon-lithium potential of hard carbon is higher than 0.2V, which makes the graphite composite negative electrode material have good safety performance.

[0029] Preferably, in step (1), the weight ratio of the graphite to the coal tar pitch is 4-10:1, preferably 6-10:1.

[0030] Preferably, in step (1), relative to 100 parts by weight of the coal tar pitch, the amount of the plasticizer is 400-1200 parts by weight, the amount of the acidic functional additive is 5-25 parts by weight, and the amount of the coupling agent is 2-4 parts by weight. The inventors have found that in this preferred case, the rate performance and high temperature storage performance of the graphite composite negative electrode material can be further improved.

[0031] Preferably, in step (1), the amount of the organic solvent I is 500-1500 parts by weight, preferably 500-1200 parts by weight, relative to 100 parts by weight of the coal tar pitch.

[0032] Preferably, in step (1), the amount of the alkaline functional additive is 5-25 parts by weight, and the amount of ethylenediamine is 1-5 parts by weight relative to 100 parts by weight of the petroleum asphalt. In this preferred case, the rate performance and high temperature storage performance of the graphite composite negative electrode material can be further improved.

[0033] Preferably, in step (1), the amount of the organic solution Ⅱ is 500-1500 parts by weight, preferably 500-1200 parts by weight, relative to 100 parts by weight of the petroleum asphalt.

[0034] Preferably, in step (1), the plasticizer is unsaturated coal tar, and the sulfur content of the unsaturated coal tar is 0.6-0.8wt%, and the relative density at 550°C is 1.15-1.2g / cm 3 ;

[0035] Preferably, the relative density of the coal tar pitch at 15°C is 1.0-1.2 g / cm 3 , ash content is 1-1.5wt%, and flash point is not less than 130℃.

[0036] Preferably, the content of sulfur in the petroleum asphalt is 0.5-2.5wt%, the content of asphaltene is 10-30wt%, and the weight average molecular weight of the colloid is 2000-6000.

[0037] Preferably, the density of the petroleum asphalt at 20°C is 0.9-1 kg / m 3 , the kinematic viscosity at 25℃ is 4000-8000mPa·s.

[0038] Preferably, in step (1), the acidic functional additive is at least one of malic acid, citric acid and lactic acid, preferably malic acid.

[0039] Preferably, the coupling agent is at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane and (3-aminopropyl)methyldiethoxysilane, preferably 3-aminopropyltrimethoxysilane.

[0040] Preferably, the organic solvent I is at least one of N-methylpyrrolidone, carbon tetrachloride and cyclohexane, preferably N-methylpyrrolidone.

[0041] Preferably, the alkaline functional additive is at least one of ammonium phosphate, melamine and polyamide, preferably ammonium phosphate.

[0042] Preferably, the organic solvent II is at least one of N-dimethylacetamide, tetrahydrofuran and N,N-dimethylacetamide, preferably N-dimethylacetamide.

[0043] Preferably, in step (1), the conditions for the first mixing and the second mixing independently include: a temperature of 25-40° C. and a time of 15-45 min.

[0044] According to a preferred specific embodiment, the method further comprises: in step (1), ball milling the coating precursor obtained by liquid phase coating to obtain the graphite coating material; more preferably, the ball milling time is 120-240 minutes.

[0045] Preferably, in step (2), the double helix electrospinning is performed by solution spinning, and the electric field voltage of the solution spinning is 15-30 kV.

[0046] The conditions for the double helix electrospinning include: a jet width of 5-25 cm, a jet flow rate of 2-7 mL / min, and a jet time of 30-120 min.

[0047] According to a preferred specific embodiment, the method further comprises: in step (2), vacuum drying the intermediate formed by double-helix electrospinning to obtain the composite fiber bundle.

[0048] Preferably, in step (3), the conditions of the pyrolysis treatment include: a temperature of 1000-1200° C. and a time of 2.5-3 h.

[0049] According to a particularly preferred embodiment, the present invention Figure 1 A flow chart of a method for preparing the above-mentioned graphite composite negative electrode material is provided, and the preparation method comprises:

[0050] (1) contacting graphite with coal tar pitch in the presence of a plasticizer to perform liquid phase coating to obtain a coated precursor, and then ball milling the coated precursor to obtain the graphite coated material;

[0051] and in the presence of organic solution ⅠⅠ, contacting petroleum asphalt with alkaline functional additive and ethylenediamine for second mixing to obtain solution B;

[0052] and contacting the graphite-coated material with an acidic functional additive and a coupling agent in the presence of an organic solvent I for first mixing to obtain a solution A;

[0053] (2) using a double helix electrospinning device to perform double helix electrospinning using the solution A and the solution B as the inner ring solution and the outer ring solution, respectively, to form an intermediate; and then vacuum drying the intermediate to obtain a composite fiber bundle;

[0054] (3) The composite fiber bundle is subjected to pyrolysis treatment to generate a carbonization reaction to obtain the graphite composite negative electrode material.

[0055] As mentioned above, the second aspect of the present invention provides a graphite composite negative electrode material prepared by the method described in the first aspect.

[0056] As mentioned above, the third aspect of the present invention provides the use of the graphite composite negative electrode material described in the second aspect in a soft-pack battery.

[0057] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the drugs and reagents used are all commercially available products.

[0058] Unsaturated coal tar: purchased from Beijing Bailingwei Technology Co., Ltd., brand 8007-45-2; the sulfur content is 0.65wt%, and the relative density at 550℃ is 1.17g / cm 3 .

[0059] Coal tar pitch: purchased from Hebei Deri New Materials Co., Ltd.; relative density at 15°C is 1.05 g / cm 3 , the ash content is 1.2wt% and the flash point is 159℃.

[0060] Petroleum asphalt: purchased from Sinopec, brand 90A; density at 20°C is 0.997 kg / m 3 , the kinematic viscosity at 25°C is 6000mPa·s; the sulfur content is 2.2wt%, the asphaltene content is 25wt%, and the weight-average molecular weight of the colloid is 4000.

[0061] In the following examples, 1 part by weight means 1 g.

[0062] In the following examples, the double helix electrospinning method is solution spinning, and the electric field voltage of the solution spinning is 20 kV; the conditions of the double helix electrospinning are: the jet width is 15 cm, the jet flow rate is 5 mL / min, and the jet time is 120 min.

[0063] The following examples are used to illustrate the method for preparing the graphite composite negative electrode material of the present invention.

[0064] Example 1

[0065] (1) In the presence of 1200 parts by weight of a plasticizer (unsaturated coal tar), graphite and 100 parts by weight of coal tar pitch are placed in a high-temperature coating machine for liquid phase coating to obtain a coated precursor; then the coated precursor is placed in a planetary ball mill for ball milling for 240 minutes to obtain a graphite coated material;

[0066] In the presence of organic solvent I (N-dimethylacetamide), the graphite-coated material is contacted with an acidic functional additive (malic acid) and a coupling agent (3-aminopropyltrimethoxysilane) to perform a first mixing (temperature of 25° C., time of 30 min), and stirred to obtain a solution A;

[0067] and in the presence of organic solution ⅠⅠ (N-methylpyrrolidone), petroleum asphalt (100 parts by weight) is contacted with an alkaline functional additive (ammonium phosphate) and 5 parts by weight of ethylenediamine to perform a second mixing (temperature of 25° C., time of 30 minutes), and stirred to obtain solution B;

[0068] (2) using solution A and solution B as the inner ring solution and the outer ring solution, respectively, and performing double helix electrospinning using a double helix electrospinning device, and vacuum drying the formed intermediate to obtain a composite fiber bundle;

[0069] (3) The composite fiber bundle is subjected to pyrolysis treatment (temperature of 1200° C., time of 3 h) to cause a carbonization reaction to obtain a graphite composite negative electrode material.

[0070] The specific raw material dosage of this example is shown in Table 1.

[0071] Examples 2 and 3 were prepared by the same method as Example 1, except that the amounts of raw materials were different, as shown in Table 1.

[0072] Table 1

[0073] Example 1 Example 2 Example 3 <![CDATA[Dosage weight ratio 1 > 4:1 8:1 10:1 Liquid coating Temperature / ℃ 250 350 400 Time / h 3 2 6 Speed / rpm 40 50 60 Organic solvent I / part by weight 500 1000 1200 Acidic functional additives / weight 5 15 25 Coupling agent / weight 4 2 3 Organic solvent ⅠⅠ / weight parts 500 1000 1200 Basic functional additives / weight 5 15 25 Solution A / weight 2000 2500 3000 <![CDATA[Dosage weight ratio 2 > 1.5:1 2:1 2.5:1 name S1 S2 S3

[0074] Note: Weight ratio 1 Refers to the weight ratio of graphite to coal tar. 2 It refers to the weight ratio of solution A and solution B.

[0075] Example 4

[0076] This embodiment is carried out in a similar manner to that of Embodiment 1, except that the amount of coal tar pitch in this embodiment is kept unchanged, the amount of plasticizer in this embodiment is adjusted to 300 parts by weight, the amount of acidic functional additive to 30 parts by weight, and the amount of coupling agent to 2 parts by weight, to obtain graphite composite negative electrode material S4.

[0077] Example 5

[0078] This example is carried out in a similar manner to that of Example 1, except that the amount of petroleum asphalt in this example is kept unchanged, the amount of the alkaline functional additive in this example is adjusted to 30 parts by weight, and the amount of ethylenediamine is adjusted to 8 parts by weight, to obtain a graphite composite negative electrode material S5.

[0079] Comparative Example 1

[0080] This comparative example was carried out in a similar manner to Example 1, except that the conditions for liquid phase coating in step (1) of this comparative example were adjusted to: temperature of 150° C., time of 8 h, and rotation speed of 30 rpm, to obtain graphite composite negative electrode material D1.

[0081] Comparative Example 2

[0082] This comparative example was carried out in a similar manner to Example 1, except that the weight ratio of solution A to solution B in step (2) of this comparative example was adjusted to 3:1, thereby obtaining a graphite composite negative electrode material D2.

[0083] The following application examples are used to illustrate the application of the graphite composite negative electrode material of the present invention in a soft pack battery.

[0084] (1) Preparation of positive electrode sheet

[0085] The positive electrode material LiFePO4 / C, conductive carbon black, and binder (PVDF) were mixed in a mass ratio of 91:4:5, 1400 mL of NMP was added as a solvent, and the slurry was evenly coated on the surface of the aluminum foil, dried at 80°C for 12 hours, and then rolled using a roller press to obtain a positive electrode sheet with a thickness of 175 μm;

[0086] (2) Preparation of negative electrode sheet

[0087] Conductive carbon black, CMC, SBR and S1 were mixed in a mass ratio of 1.5:2.5:2:94, 1000 mL of water was added as a solvent, and the slurry was evenly coated on both sides of the copper foil, dried at 80°C for 12 hours, and rolled with a roller press to obtain a negative electrode sheet with a thickness of 125 μm;

[0088] (3) Assemble into soft pack battery

[0089] Celgard2400 polypropylene porous membrane was used as the separator, 1 mol / L LiPF6 / (EC+DEC+DMC) (the volume ratio of EC, DEC and DMC was 1:1:1) was used as the electrolyte, and a 5Ah soft-pack battery Y1 was assembled according to conventional processes.

[0090] Application Example 2 to Application Example 5

[0091] The method is similar to that of Application Example 1, except that S1 in Application Example 1 is replaced by S2, S3, S4, and S5, respectively, to obtain soft-pack batteries Y2, Y3, Y4, and Y5.

[0092] Comparative Application Example 1 to Comparative Application Example 2

[0093] The method is similar to that of Application Example 1, except that S1 in Application Example 1 is replaced by D1 and D2, respectively, to obtain soft-pack batteries DY1 and DY2.

[0094] Comparative Application Example 3

[0095] A method similar to that of Application Example 1 is used, except that S1 in Application Example 1 is replaced with graphite of the prior art to obtain a soft-pack battery DY3.

[0096] Test Case

[0097] All soft-pack batteries obtained in the corresponding use cases were subjected to performance tests, including high-temperature storage performance and battery rate performance, with a voltage range of 2.0-3.65V and a temperature of 55°C. The high-temperature storage results are shown in Table 2, and the battery rate performance is shown in Table 3.

[0098] The test methods involved are as follows:

[0099] Charge and discharge capacity: obtained by using a 5V10A-80CH charge and discharge instrument produced by Ningbo Bait Measurement and Control Technology Co., Ltd. to test the battery charge and discharge.

[0100] Capacity retention rate: obtained by testing the battery using a 5V300A / 5V600A charge and discharge instrument produced by Shenzhen Shenghong Electric Co., Ltd.

[0101] Table 2

[0102] sample Storage 1C discharge capacity (Ah) Capacity retention rate on the 7th day (%) Capacity retention rate on the 21st day (%) Y1 5.00 99.64 99.03 Y2 5.00 99.79 99.21 Y3 5.00 99.85 99.45 Y4 5.00 97.83 96.88 Y5 5.00 97.69 96.58 DY1 5.00 92.47 88.57 DY2 5.00 92.54 88.77 DY3 5.00 86.1 79..3

[0103] Table 3

[0104]

[0105] From the above results, it can be seen that the high temperature storage performance is ranked as follows: Y3>Y2>Y1>Y4>Y5>DY2>DY1>DY3, and the battery rate performance is ranked as follows: Y3>Y2>Y1>Y5>Y4>DY2>DY1>DY3. This shows that the high temperature storage performance and rate performance of the graphite composite negative electrode material prepared by the method for preparing the graphite composite negative electrode material provided by the present invention are significantly higher than those of the comparative example, and the graphite composite negative electrode material prepared in Example 3 has the best effect.

[0106] Therefore, the method for preparing the graphite composite negative electrode material provided by the present invention can effectively improve the rate performance and high-temperature storage performance of the traditional graphite negative electrode.

[0107] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a graphite composite negative electrode material, characterized in that: The method includes: (1) contacting graphite with coal tar pitch in the presence of a plasticizer to perform liquid phase coating to obtain a graphite-coated material; and contacting the graphite-coated material with an acidic functional additive and a coupling agent in the presence of an organic solvent I to perform a first mixing to obtain a solution A; and contacting petroleum asphalt with an alkaline functional additive and ethylenediamine in the presence of an organic solution ⅠⅠ to perform a second mixing to obtain a solution B; (2) performing double helix electrospinning using the solution A and the solution B as the inner ring solution and the outer ring solution, respectively, to obtain a composite fiber bundle; (3) The composite fiber bundle is subjected to pyrolysis treatment to obtain the graphite composite negative electrode material. Wherein, in step (1), the liquid phase coating conditions include: temperature of 250-400°C, time of 2-6h, and rotation speed of 40-60rpm; In step (2), the weight ratio of solution A to solution B is 1.5-2.5:

1.

2. The method according to claim 1, wherein: In step (1), relative to 100 parts by weight of the coal tar pitch, the amount of the plasticizer is 400-1200 parts by weight, the amount of the acidic functional additive is 5-25 parts by weight, and the amount of the coupling agent is 2-4 parts by weight.

3. The method according to claim 1 or 2, wherein: In step (1), relative to 100 parts by weight of the petroleum asphalt, the amount of the alkaline functional additive is 5-25 parts by weight, and the amount of the ethylenediamine is 1-5 parts by weight.

4. The method according to any one of claims 1 to 3, wherein: The plasticizer is unsaturated coal tar, and the sulfur content of the unsaturated coal tar is 0.6-0.8wt%, and the relative density at 550°C is 1.15-1.2g / cm 3 ; And / or, the relative density of the coal tar pitch at 15°C is 1.0-1.2 g / cm 3 , ash content is 1-1.5wt%, flash point is not less than 130℃; And / or, the content of sulfur in the petroleum asphalt is 0.5-2.5wt%, the content of asphaltene is 10-30wt%, and the weight average molecular weight of the colloid is 2000-6000.

5. The method according to any one of claims 1 to 4, wherein: The acidic functional additive is at least one of malic acid, citric acid and lactic acid; The coupling agent is at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane and (3-aminopropyl)methyldiethoxysilane; The organic solvent I is at least one of N-methylpyrrolidone, carbon tetrachloride and cyclohexane; The alkaline functional additive is at least one of ammonium phosphate, melamine and polyamide; The organic solvent Ⅱ is at least one of N-dimethylacetamide, tetrahydrofuran and N,N-dimethylacetamide.

6. The method according to any one of claims 1 to 5, wherein: In step (1), the weight ratio of the graphite to the coal tar pitch is 4-10:

1.

7. The method according to any one of claims 1 to 6, wherein: In step (2), the double helix electrospinning is performed by solution spinning, and the electric field voltage of the solution spinning is 15-30 kV.

8. The method according to any one of claims 1 to 7, wherein: In step (3), the conditions of the pyrolysis treatment include: a temperature of 1000-1200° C. and a time of 2.5-3 h.

9. A graphite composite negative electrode material prepared by the method according to any one of claims 1 to 8.

10. Use of the graphite composite negative electrode material according to claim 9 in a soft-pack battery.

Citation Information

Patent Citations

  • Soft carbon coated hard carbon composite material and preparation method thereof

    CN117117126A